STRATEGI GURU BAHASA INDONESIA DALAM MENGATASI KESULITAN MEMBACA KOSAKATA SISWA KELAS II SDN ROUTA KABUPATEN KONAWE - Ummi Kalsum; Subaedah; Muh. Aidil Sudarmono R; Martini; Muhammad Syahrul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the strategies employed by the Indonesian language teacher to address vocabulary reading difficulties among second-grade students at SDN Routa, Konawe Regency, and to identify the factors hindering this process. The study employs a qualitative approach and is classified as field research. The research subjects consist of the Indonesian language teacher and second-grade students. Data collection was conducted through observation, interviews, and documentation, while data analysis involved data reduction, data presentation, and conclusion drawing. The results indicate that the teacher implements two primary strategies: the